Chromosome status and yield characteristics of soybean (Glycine max L. (Merr)) in saline soil as affected by induced mutation - Agus Pernando Simanjuntak; Diana Sofia Hanafiah; Luthfi Aziz Mahmud Siregar (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2021)
To fulfill the demand of soybeans, the expansion of the planting area can be one of the choices through the conversion of marginal land by utilizing suboptimal land, such as saline soil. One of the plant breeding techniques to obtain tolerant plants to salinity is the use of chemical mutations, such as colchicine. The study aimed to reveal the effect of salinity on the characters of soybean plants (mutated with colchicine) and the effect of colchicine on the number of chromosomes and ploidy level. This study was conducted from January to March 2020 and carried out in the plastic house of Faculty of Agriculture, Universitas Sumatera Utara. The experiment was arranged in a Randomized Block Design with salinity levels (0 dS.m-1, 2 dS.m-1, 4 dS.m-1, 6 dS.m-1) as treatments and consisted of ten replications in each treatment. The result showed that the soybean plants were not successfully induced by colchicine at a concentration of 0.04 % with soaking duration of 10 hours, as indicated by the number of chromosomes and analysis of ploidy level. The soybeans that had been induced were planted in saline soil. There were significant effects observed on the productive branch, number of filled pods, and the weight of seeds per plant. Colchicine treatment did not successfully affect the number of chromosomes of soybeans but had an impact on the chromosome pattern. In addition, the salinity treatment of 4 dS.m-1 significantly affected the number of filled pods compared to the treatment of 6 dS.m-1.